The Stem Cell Niche in Leaf Axils Is Established by Auxin and Cytokinin in Arabidopsis . Issue 5 (21st May 2014) - Wang, Ying; Wang, Jin; Shi, Bihai; Yu, Ting; Qi, Jiyan; Meyerowitz, Elliot M.; Jiao, Yuling
Abstract : Branch meristems allow plants to form ramifying systems with new cycles of growth and development. This work shows that the establishment of axillary meristems is regulated by two classical phytohormones, with auxin suppressing and cytokinins promoting axillary meristem initiation. Abstract: Plants differ from most animals in their ability to initiate new cycles of growth and development, which relies on the establishment and activity of branch meristems harboring new stem cell niches. In seed plants, this is achieved by axillary meristems, which are established in the axil of each leaf base and develop into lateral branches. Here, we describe the initial processes of Arabidopsis thaliana axillary meristem initiation. Using reporter gene expression analysis, we find that axillary meristems initiate from leaf axil cells with low auxin through stereotypical stages. Consistent with this, ectopic overproduction of auxin in the leaf axil efficiently inhibits axillary meristem initiation. Furthermore, our results demonstrate that auxin efflux is required for the leaf axil auxin minimum and axillary meristem initiation. After lowering of auxin levels, a subsequent cytokinin signaling pulse is observed prior to axillary meristem initiation. Genetic analysis suggests that cytokinin perception and signaling are both required for axillary meristem initiation. Finally, we show that cytokinin overproduction in the leaf axil partially rescue axillary meristem initiation-deficient mutants. These results define a mechanistic framework for understanding axillary meristem initiation.